Native-speakerism and English without Borders Program: investigating language ideologies through a language policy - Passoni, Taisa Pinetti (BELT - Brazilian English Language Teaching Journal, 2017)
English without Borders (EwB) is a Brazilian government-sponsored Program created to enhance linguistic proficiency of potential candidates for outward mobility. Assuming that language ideologies embody as well as are embodied by language policies, this paper aims at examining the native-speakerism ideology. It draws on texts comprising instances of enactment and interpretations of EwB in addition to evidences posed by decisions arising from its implementation to examine how native-speakerism is positioned through the Program. Building on critical language policy approach, it employs critical discourse analysis resources to investigate how native-speakerism is challenged or reinforced by the agenda implemented by EwB. Evidences point to the overlapping of deconstructing and corroborating perspectives, especially regarding local interpretations posed by the Language Center coordinators whose considerations about the linguistic diversity of English are marked by ambivalent thoughts on the issue. The coexistence of such tensions indicates the pervasive nature of native-speakerism concerning English in Brazil.